Evaluation of the effect of carboxy methyl cellulose coating incorporated with Origanum vulgare L. and Trachyspermum Copticum nanoemulsions on shelf life extention of refrigerated ostrich meat - Raeisi, Mojtaba; Mohammadi, Bahador Haji; Coban, Ozlem Emir; Aman Mohammadi, Masoud (Springer, 2026)
This study evaluated the antimicrobial and sensory effects of carboxymethyl cellulose (CMC) coatings containing nanoemulsions of Origanum vulgare (oregano) and Trachyspermum copticum (ajowan) essential oils (EOs) on ostrich meat stored at 4 degrees C for 9 days. In vitro, both EOs showed broad-spectrum antibacterial activity against Gram-positive and Gram-negative bacteria, mainly due to phenolic compounds such as carvacrol and thymol. Oregano EO generally produced larger inhibition zones in well diffusion assays, while ajowan EO was more effective against selected strains in disc diffusion assays. When applied to meat, EO-nanoemulsion CMC coatings significantly reduced counts of aerobic mesophilic bacteria, aerobic psychrotrophic bacteria, coliforms, and molds and yeasts (p < 0.05) compared with controls. Based on the accepted spoilage threshold of 7 log CFU/g and a sensory rejection score of 5/9, the coatings extended microbiological shelf life by approximately 4 days. By day 9, the 2% oregano (M2) and ajowan (Z2) coatings achieved the lowest mesophilic counts (6.70 and 6.94 log CFU/g, respectively), demonstrating dose-dependent efficacy. Sensory evaluation indicated that oregano EO treatments (M1 and M2) better preserved odor and texture, although higher EO levels slightly reduced color scores. Objective instrumental color parameters (L, a, b*, hue angle) were not measured, which is recognized as a limitation.
Keywords: Antimicrobial activity; Biopolymer coatings; Edible films; Food safety; Meat quality; Natural preservatives; Refrigerated storage; Sensory evaluation